An Analysis of Bank Loan Rate Indexation - JAMES, CHRISTOPHER (Journal of Finance, 1982)
ABSTRACT This paper examines the economic rationale for the use of bank loan commitments and the effect on the allocation of bank credit of indexing the loan rate offered through the commitment to the prime. A simple model of the loan market is constructed and used to examine the effect changes in loan demand and the cost of bank funds have on the allocation of bank credit under indexation. It is shown that indexing implies changes in the relative cost of borrowing for certain groups of bank customers. For nonprime customers, an increase in the cost of bank funds results in a decline in the relative cost of borrowing under commitments. The pattern of commitment use is found to be consistent with the predictions of the model.